KEYBOARD JIHADIST? - May, Michael (American Prospect, 2012)
The article focuses on Tarek Mehanna, a 29-year-old Egyptian American prosecuted for terrorism. It states that the case of Mehanna represented a fundamental departure from the hundreds of domestic terrorism prosecutions in the U.S. after the terrorist attack on September 11, 2001. Prosecutors accused Mehanna of being part of media wing of al-Qaeda and that Mehanna intended to inspire jihad through his keyboard.